Dangdut Koplo Song Lyrics as A Source of Learning The Value of Character In Social Studies Learning in Junior High Schools - Mengkepe, Amy Dara Istikoma; Sarmini, Sarmini; Nasution, Nasution (International Journal for Educational and Vocational Studies, 2020)
This study intends to describe the content of values in the lyrics of the song dangdut koplo as a source of learning the value of characters in social studies learning in junior high school. The dangdut koplo music genre that is increasingly in demand by listeners from all ages of children to adults has song lyrics that are close to the theme of everyday social life. This type of research is qualitative with descriptive methods. This study uses a qualitative approach to content analysis conducted on three dangdut koplo song titles (Bojo Galak, Bidadari Kesleo, and Pegaten Bojomu) with the most listeners. Based on the results of the analysis and discussion of the data shows that each of the lyrics of the song dangdut koplo entitled Bojo Galak, Bidadari Kesleo, and Pegaten Bojomu show the values of tolerance, honesty, responsibility, independent, and peace-loving character. The dangdut koplo song lyrics have themes that are close to the daily lives of students and contain some good character values, so it is recommended that teachers can use the dangdut koplo song lyrics as a source of learning the character values in junior high school social studies learning integrated with adjusting the contents of the song with the material which will be taught by the teacher.